Degenerated Hopf bifurcation in the Fitzhugh-Nagumo system. 2. Bautin bifurcation - Rocşoreanu, Carmen; Giurgiţeanu, Nicolaie; Georgescu, Adelina (Rev. Anal. Numér. Théor. Approx., 2000)
The results on the Hopf bifurcation obtained in [1] are completed with those concerning the degenerated Hopf bifurcation of Bautin type. They are deduced by normal forms technique and concern a biodynamical system related with Van der Pol oscillator. Numerical investigations carried out by methods from [2] are also reported.